Eukaryotic phytoplankton community spatiotemporal dynamics as identified through gene expression within a eutrophic estuary. (19th February 2018) - Gong, Weida; Paerl, Hans; Marchetti, Adrian
Summary: Over the span of a year, we investigated the interactions between biotic and abiotic factors within the eutrophic Neuse River Estuary (NRE). Through metatranscriptomic sequencing in combination with water quality measurements, we show that there are different metabolic strategies deployed along the NRE. In the upper estuary, taxonomically resolved phytoplankton groups express more transcripts of genes for synthesis of cellular components and carbon metabolism whereas in the lower estuary, transcripts allocated to nutrient metabolism and transport were more highly expressed. Metabolisms for polysaccharide synthesis and transportation were elevated in the lower estuary and could be reflective of unbalanced growth and/or interactions with their surrounding microbial consortia. Our results indicate phytoplankton have high metabolic activity, suggestive of increased growth rates in the upper estuary and display patterns reflective of nutrient limitation in the lower estuary. Among all the environmental parameters varying along the NRE, nitrogen availability is found to be the main driving factor for the observed spatial divergence.